系統思考能力的分析架構、評量與教學：K-12 科學教育相關 實徵性研究之文獻回顧 - 林英杰 Ying-Chieh Lin; 李文瑜 Silvia Wen-Yu Lee; 莊秋蘭 Chiu-Lan Chuang (National Changhua University of Education, 2022)
研究旨在透過文獻分析，回顧過去國外科學教育領域中的系統思考能力相關研究，歸納其適用年級與學科、系統思考能力分析架構，以及評量與教學的趨勢並提出建議。研究者於 SCOPUS 與 Web of Science 資料庫搜尋 2000 年到 2019 年的英文期刊論文，經有系統篩選後，針對 20 篇文章進行分析。分析結果發現，系統思考的研究對象以國、高中生為主，有些研究以小學生為對象，其學習成效主要在基礎系統思考能力的獲得。涉及的學科領域則以生態、生物以及地科最為常見，所回顧的文獻中並沒有應用於物理領域，顯示系統思考並非適合融入所有自然科學領域。對於系統思考能力的分析架構，共可歸納出組件連結模式、階層發展模式、複雜系統模式及內容導向模式等四種類型。在系統思考量測方法上許多研究採多元評量，最常被採用的是開放性試題與晤談。至於教學策 略，許多研究都採取了多元的教學活動，且多半包含知識統整活動，部分研究則採用電腦模擬進行教學。由於文獻中已有較為完整的系統思考能力分析架構，未來建議可以進行學習進程或是縱貫性研究，並將資訊科技應用於系統思考評量上。最後，我們對系統思考在教學與評量的實務建議包含有：教學上應優先嘗試初階的組件連結模式；教學方法則以明示教學法協助學生建立系統思考概念鷹架、嘗試採用多元的活動設計、引進科技輔助以及引導學生廣泛地將系統思考應用於各種生活情境中；評量方面則是建議以概念圖、概念繪圖及概念填空題進行，容易實施且能獲得較多訊息。 The aim of this research was to review past empirical studies about systems thinking in science education in order to understand the applied grade levels and subject areas, the analytical framework for systems thinking, and its trends in teaching and assessment. We searched for research articles published from 2000 to 2019 in the SCOPUS and Web of Science database and found 20 qualified studies. The results showed that most studies were conducted at junior high schools and senior high schools. Some studies were conducted at the elementary school level and found gains in fundamental competence of systems thinking. The most frequently applied subject areas were ecology, biology, and earth science. In this review, no studies applied systems thinking in physics. This indicates that systems thinking might not be suitable for all subject areas of science. In terms of the analytical framework for systems thinking, different studies invented different frameworks. The common features of the systems thinking framework include components recognition, as well as the mutual interactions and influence of different components. Regarding assessment for systems thinking, some studies used multiple assessments, and the most commonly used types of assessments were open-ended questions and interviews. Many studies adopted a variety of teaching activities and included knowledge integration activities. Some studies also used computer simulations to support learning. For future research, we suggest investigating the learning progression of systems thinking or conducting longitudinal studies by applying the available analytical framework of systems thinking. Future studies can also apply computer technology in the assessment of systems thinking. Finally, we offer some specific suggestions for teaching and assessments of systems thinking.